2007
DOI: 10.1002/pits.20276
|View full text |Cite
|
Sign up to set email alerts
|

The school‐based health center as a resource for prevention and health promotion

Abstract: The importance of school‐based health centers (SBHCs) in overall prevention and health promotion programming is growing as they become increasingly common in schools. SBHCs can improve access to comprehensive physical and mental health services for children and families, and make a significant contribution to universal prevention efforts in schools. Partnering with school‐based health centers in the overall prevention and health promotion programming provides an opportunity for school psychologists to broaden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 32 publications
1
20
0
5
Order By: Relevance
“…Multiprofessional collaboration has a lot of advantages in making a more effective problemsolving and intervention-generating process compared to isolated individual achievements (e.g., Brown & Bolen, 2008;Cook et al, 2001;Poulton & West, 1999;Toseland et al, 1986), and my findings confirm this by pointing to advantages when such collaboration functions well. Nevertheless, my findings also confirm other research (e.g., Robinson, 2002;SlonskiFowler & Truscott, 2004;Spratt et al, 2006) that indicates that problems and pitfalls easily might arise when teachers and other professionals interact with each other and with students and their parents.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Multiprofessional collaboration has a lot of advantages in making a more effective problemsolving and intervention-generating process compared to isolated individual achievements (e.g., Brown & Bolen, 2008;Cook et al, 2001;Poulton & West, 1999;Toseland et al, 1986), and my findings confirm this by pointing to advantages when such collaboration functions well. Nevertheless, my findings also confirm other research (e.g., Robinson, 2002;SlonskiFowler & Truscott, 2004;Spratt et al, 2006) that indicates that problems and pitfalls easily might arise when teachers and other professionals interact with each other and with students and their parents.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, implementation of multiprofessional school-based health care services has shown to (a) have positive effects on students' academic achievement (Brown & Bolen, 2008;Shaw, Kelly, Joost, & Parker-Fisher, 1995), (b) reduce absence from school (Gall, Pagano, Desmond, Perrin, & Murphy, 2000), and (c) reduce aggressive as well as substance use behaviors among students (see Brown & Bolen, 2008). Nevertheless, research on multiprofessional teams and collaboration in school settings has shown a lot of pitfalls or problems:…”
mentioning
confidence: 99%
“…Schools are thought to be the most important environment to provide health information to children in order to achieve the goal of health education program, as children in school are relatively accessible and already in learning environment. 25 It has also been found that learning is enhanced by establishing a fixed time and place. 26 Access to school library and knowledge of school teachers provide additional benefits in teaching these children.…”
Section: Discussionmentioning
confidence: 99%
“…The school-based health center (SBHC) is another model that represents an important interdisciplinary approach to providing comprehensive physical and mental health care for students. SBHCs typically deliver primary care services and may include reproductive, dental, and acute care services for students and may also coordinate with external community providers (Brown & Bolen, 2008). …”
Section: Introductionmentioning
confidence: 99%